2015
DOI: 10.1038/onc.2015.296
|View full text |Cite|
|
Sign up to set email alerts
|

Oncoprotein ZNF322A transcriptionally deregulates alpha-adducin, cyclin D1 and p53 to promote tumor growth and metastasis in lung cancer

Abstract: ZNF322A encoding a classical Cys2His2 zinc finger transcription factor was previously revealed as a potential oncogene in lung cancer patients. However, the oncogenic role of ZNF322A and its underlying mechanism in lung tumorigenesis remain elusive. Here we show ZNF322A protein overexpression in 123 Asian and 74 Caucasian lung cancer patients. Multivariate Cox regression analysis indicated that ZNF322A was an independent risk factor for a poor outcome in lung cancer, corroborating the Kaplan–Meier results that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“… 7 , 10 , 25 , 26 However, the critical factors that regulate CSC maintenance in HCC remain largely unknown. Recent studies have revealed that aberrant expression of zinc finger proteins contributes to progression in multiple cancers, including tumorigenicity, metastasis and chemoresistance, 27 , 28 , 29 which the CSC subpopulation might regulate. Here, we found that ZNF687 overexpression markedly promoted HCC cell tumorsphere formation capability and increased the HCC SP + /CD133 + populations in vitro .…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 10 , 25 , 26 However, the critical factors that regulate CSC maintenance in HCC remain largely unknown. Recent studies have revealed that aberrant expression of zinc finger proteins contributes to progression in multiple cancers, including tumorigenicity, metastasis and chemoresistance, 27 , 28 , 29 which the CSC subpopulation might regulate. Here, we found that ZNF687 overexpression markedly promoted HCC cell tumorsphere formation capability and increased the HCC SP + /CD133 + populations in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…They found that ZNF322A formed a complex with c-Jun and cooperatively activated ADD1 and CCND1 but repressed p53 gene transcription. Reconstitution experiments indicated that CCND1 and p53 were important to ZNF322A-mediated promotion of cell proliferation, whereas ADD1 was necessary for ZNF322A-mediated cell migration and invasion, suggesting ADD1 was involved in tumorigenesis and metastasis of lung cancer [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a subtype of colorectal cancer at a special anatomical site, LRC is characterized by its specific biological behavior. TP53 is one of the most important cancer suppressor genes, and structural variation and abnormal expression of p53 have been identified to be associated with numerous cancer types (22)(23)(24)(25). However, the associations between TP53 gene polymorphisms and protein expression, and the association of p53 protein expression with the biological behavior and prognosis of LRC have not been clearly investigated.…”
Section: Discussionmentioning
confidence: 99%